Interdependencies in the euro area derivatives clearing network: A multi-layer network approach - Simonetta Rosati; Francesco Vacirca (European Central Bank (ECB), 2019)
The global nature of derivatives markets, and the presence of large key financial institutions trading in several markets across the globe, call for taking a "macro" view on the interconnections arising in the clearing network. Based on the analysis of derivatives transactions data reported under the EMIR Regulation we reconstruct the network of relationships in the centrally-cleared derivatives market and analyse its topology providing insight into its structural features. The centrally-cleared derivatives network is modelled in the form of a multiplex network where each layer is represented by a derivatives asset class market. In turn, each node represents a single counterparty in that market. On the basis of different centrality measures applied to the collapsed aggregate and to the multiplex network, the critical participants of the euro area centrally-cleared derivatives market are identified and their level of interconnectedness analysed. This paper provides insight on how the collected data pursuant to the EMIR regulation can be used to shed light on the complex network of interrelations underlying the financial markets. It provides indications on structural features of the euro area centrally-cleared derivatives market and discusses policy relevant implications and future applications.
Keywords: G01; G15; G23; 330; Interconnectedness; CCP; multiplex network; derivatives markets; EMIR data